2018
DOI: 10.1089/ast.2017.1732
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and Inhibitory Activities of Minerals for Alanine Oligopeptide Elongation Under Hydrothermal Conditions

Abstract: In a previous study, we have showed that the elongation of an alanine oligopeptide [L-alanyl-L-alanyl-L-alanyl-L-alanine ((Ala))] to higher oligopeptides is enhanced by calcite and dolomite at 275°C, using a mineral-mediated hydrothermal flow reactor system. However, a problem during the use of hydrothermal flow reactor system was that some of the minerals, such as clay, could not be tested due to their clogging in the reactor. In this article, we attempted to analyze the scope of enhancement for the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…41 In relation to our alkaline hydrothermal system with a high abundance of CO 2 , the presence of carbonate minerals such as calcite and dolomite have been shown to promote peptide formation. 42,43 In our experiment, the formation of calcite was only confirmed under the presence of amino acids (Figure 1), suggesting that mineral−organic interaction has likely taken place.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…41 In relation to our alkaline hydrothermal system with a high abundance of CO 2 , the presence of carbonate minerals such as calcite and dolomite have been shown to promote peptide formation. 42,43 In our experiment, the formation of calcite was only confirmed under the presence of amino acids (Figure 1), suggesting that mineral−organic interaction has likely taken place.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Recent studies have shown that magnetite can alter the thermodynamic equilibrium of the system and greatly enhance the formation of the liner dimer while decreasing the amount of the diketopiperazines (DKP) under hydrothermal conditions . In relation to our alkaline hydrothermal system with a high abundance of CO 2 , the presence of carbonate minerals such as calcite and dolomite have been shown to promote peptide formation. , In our experiment, the formation of calcite was only confirmed under the presence of amino acids (Figure ), suggesting that mineral–organic interaction has likely taken place.…”
Section: Resultsmentioning
confidence: 91%